Evidence for the Indonesian origins of certain elements of African culture: A review, with special reference to the arguments of A.M. Jones - Blench, Roger (International Library of African Music, 1982)
The hypothesis that sea-going peoples from the general area of present-day Indonesia contributed to the formation of various aspects of African culture, and in particular to aspects of material culture, continues to be a controversial topic in African studies, and the prominent contribution by ethnomusicologists to the argument makes it of special interest to students of African music. Since it was first formulated by Frobenius at the end of the last century (Frobenius, 1898: a convenient English summary in Frobenius, 1900), new evidence has been adduced by von Hornbostel, (1964, 1971 and 1972). It is not my intention to deal with all the literature on this subject, but rather to focus on musicological and related topics and to scrutinise the validity of the style of argument employed by these authors.
Keywords: African Music